2022
DOI: 10.1002/rcm.9352
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray ionization in‐source decay of N‐glycans and the effects on N‐glycan structural identification

Abstract: Rational Electrospray ionization (ESI) and matrix‐assisted laser desorption ionization (MALDI) are soft ionization techniques commonly used in mass spectrometry. Although in‐source and post‐source decays of MALDI have been investigated extensively, the analogous decays of ESI have received little attention. Previous studies regarding the analogous decays of ESI focus on the dissociation of multiply charged proteins and peptides. The decay of carbohydrates in ESI has not been investigated yet, and it may have i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…These N -glycans were then sent into two-dimensional HPLC for further purification and isomer separation. A study demonstrated that approximately 1% of N -glycans undergo in-source decay and crack into small N -glycans during the ionization process of electrospray ionization . If a high concentration of large N -glycans is mixed with a low concentration of small N -glycans in the ESI solution, ESI in-source decay of large N -glycans may interfere with the structural identification of small N -glycans.…”
Section: Resultsmentioning
confidence: 99%
“…These N -glycans were then sent into two-dimensional HPLC for further purification and isomer separation. A study demonstrated that approximately 1% of N -glycans undergo in-source decay and crack into small N -glycans during the ionization process of electrospray ionization . If a high concentration of large N -glycans is mixed with a low concentration of small N -glycans in the ESI solution, ESI in-source decay of large N -glycans may interfere with the structural identification of small N -glycans.…”
Section: Resultsmentioning
confidence: 99%
“…Next, the N -glycans were separated according to their sizes by HPLC using a TSKgel Amide-80 column; the chromatogram is shown in Figure (a). The separation of N -glycans by different sizes avoids the interference in structural determination of small N -glycans by large N -glycans due to the ESI in-source decay . For example, Figure (a) shows that the retention time of 19–23 min mainly consists of Man 6 GlcNAc 2 ( m / z 1419) and a small amount of Man 5 GlcNAc 2 ( m / z 1257).…”
Section: Resultsmentioning
confidence: 99%
“…The CID sequences in LODES were derived from carbohydrate dissociation mechanisms [42][43][44][45] . LODES enables us to determine the D, E, F, and G, according to the dissociation mechanisms of hexose [27][28][29][30][31][41][42][43] .…”
Section: A Databases Of Man N Glcnac 2 (N=5 6 7) Isomersmentioning
confidence: 99%
“…The amide-80 column separated N-glycans into different sizes, as illustrated in Fig. 2(a), to eliminate the interference by ESI in-source decay 41 . The fractions collected from the eluents of amide-80 column were sent into the second HPLC using a PGC Hypercarb column (2.1 mm × 100 mm, particle size of 3 µm, Thermo Fisher Scientific, Waltham, MA, USA) for N-glycan isomer separation.…”
Section: (D) Separation Of N-glycan Isomersmentioning
confidence: 99%
See 1 more Smart Citation